Implementasi Blockchain Pada Bidang Keunagan Digital - Ramadan, Zeinan; Supriadi, Fidi; Junaedi, Dani Indra (Dinasti Review Publisher, 2025)
This research aims to spread the implementation of blockchain technology in the digital financial sector through a literature study approach. The main issue raised is how blockchain is applied in financial services and what challenges and benefits come with it. The method used was a literature review of 18 relevant scientific articles. The analysis results show that blockchain has been implemented in four main categories, namely cryptocurrency, cross-border payments, decentralized finance (DeFi), and smart contracts. This implementation provides significant benefits such as transparency, cost and time efficiencies, and increased security. However, blockchain implementation still faces serious challenges such as regulatory ambiguity, scalability issues, cybersecurity risks, and low adoption by traditional financial institutions. This research suggests the importance of strengthening regulations, technical innovation, and increasing technological literacy to encourage broader and more effective blockchain implementation in digital financial systems.